Moderating roles on individuals' decisions when making choices for others. (January 2015) - Lin, Hung-Chou
Highlights: People incorporated more variety seeking for others than for themselves. Gender moderates the effects of self–other differences on variety seeking. Self-monitoring moderates the effects of self–other differences on variety seeking. Maximizing tendency moderates effects of self–other differences on variety seeking. Abstract: Previous studies have demonstrated that when the social context entails possible public scrutiny, consumers may change their judgments and choices to what is perceived to be socially desirable, while they may incorporate more variety seeking when they are making choices for others rather than for themselves. Building upon previous research and in an attempt to better understand consumers' variety-seeking tendencies, this study aims to uncover the underlying mechanisms for the self–other difference in the variety seeking tendency via experimental designs. This article discusses individual differences of gender, self-monitoring and maximizing tendency with respect to self–other differences when consumers incorporate variety seeking. Consistent with the proposed hypotheses, the results indicate that the individuals' differences tested in this article moderate the effects of self–other differences on variety seeking. Finally, the academic and practical implications are addressed.